(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Political empowerment supports creating policies that would best support gender equality and agency for women in both the public and private spheres. Methods that have been suggested are to create affirmative action policies that have a quota for the number of women in policy making and parliament positions. and the study which discussed about Historical Background of Women Empowerment, Women Empowerment in India , Women Empowerment through Education, Participation of Women in the Post-Independent Period, Political Participation before Independence, Historical Background of Women Empowerment, Women’s Political Participation, The Non-Participants (Women), Political Participation, Concept of Women Empowerment, Concept of Empowerment, Empowerment.